WAWASAN KEBANGSAAN DALAM BINGKAI PEMBERITAAAN SEBAGAI STRATEGI MANAJEMEN KONFLIK UNTUK MENGUATKAN MODERASI BERAGAMA - Petrus Imam Prawoto Jati (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Indonesia is a country consisting of various ethnic groups, cultures, languages, beliefs, customs and various other attributes of difference. It can be said that diversity is the face of the Indonesian nation itself. This is confirmed by the motto of the Indonesian nation, namely Bhinneka Tunggal Ika, which has been proclaimed since the time of the Majapahit Kingdom in the 14th century. In another perspective, the face of the Indonesian nation is the potential for enormous division and conflict. One of the most easily ignited potential conflicts is about religious issues. Due to the spirit of spreading religion and defending the truth in an inclusive manner, conflicts in Indonesian society are often triggered because of religious issues. This potential is also often deliberately triggered by certain parties for economic, political, and personal or group interests. Often this conflict in the community is exacerbated by unprofessional, one-sided reporting, or focusing on sensationalism to increase the number of readers or viewers. The commercial side of the media industry must be balanced with the spirit of national insight from the media workers themselves as a means of control in reporting on religious conflicts. National insight itself is a concept or perspective of this nation on itself which aims to build and develop unity and integrity. This spirit of national insight should be rekindled in the community, especially among journalists and the media as a means of conflict management in religious moderation in Indonesia.